The study of dental pulp stem cells following restorative procedures on deciduous molars - Alaa Nasser, Abed Al Rahman Lutfi (2009)
The biological examination of pulp injury, repair events and the response of dental pulp stem cells to dental restorative matetials is of paramount importance for understanding the post operative development and the use of these repair activities to accomplish restorative treatment. The objectives of this study were to compare the stem cells proliferative activity using colorimetric proliferation reagent alamarblue® and to evaluate their response by comparing the Tertiary Dentin Thickness (TDT) fonnation using Haematoxyline and Eosin staining for histological examination following restorative procedures on deciduous molars. Healthy paediatric dental patients aged between 9 to 11 years with caries deciduous molars without pulpal exposure, who attended the paediatric dental clinic for dental treatment in the School of Dental Sciences, Health Campus, Universiti Sains Malaysia, were selected. The teeth were divided into two groups; Group 1 comprised of 29 teeth filled with Glass Ionomer Cement (GIC) alone and Group 2 with 29 teeth, lined with Calcium hydroxide (Ca(OH)2) cement and filled with GIC. The teeth were reviewed for up to 6 months before being extracted according to standardized procedures based on the selected criteria. A total of 34 teeth were extracted with 17 teeth belonging to each group. In each study group 7 teeth were assigned for stem cell culture and 10 teeth were subjected to histological sections. The results showed that stem cells from human extracted deciduous teeth (SHED) were positive for surface antigenic markers, CD 105 and CD1 66 following immunocytochemistry test. The proliferative activity (Median, IQR) for Group 1 (38,19) was less as compared to Group 2 (41,19) and it was not significant (p>O.OS). However, TDT area (Median, IQR) in Group 2 (0.15,0.033) was higher as compared to Group I (0.05,0.013) and it was significant (p<O.OOI). The pulp of deciduous teeth contains stem cell population, which respond well and maintains proliferative activity following restorative procedures using Ca(OH)2 cement and GIC. However, these matetials create different response in tertiary dentin deposition, where the reactionary dentin deposition appeared to be more under restorations lined with Ca(OH)2. Thus Ca(OH)2 cement has high credibility to be used in deep cavities for pulp protection.